LOW PREVALENCE OF COVID-19 IN LAOS AND CAMBODIA: DOES DIET PLAY A ROLE? - Geir Bjorklund; Roman Lysiuk; Monica Butnariu; Larysa Lenchyk; Vineet Sharma; Rohit Sharma; Natalia Martins (Acta Medica Leopoliensia)
The study aims to review the involvement of different dietary habits in Laotian, Cambodian, and Vietnamese populations in reducing COVID19 impact.